Prospective Cardiovascular Surveillance of Immune Checkpoint Inhibitor–Based Combination Therapy in Patients With Advanced Renal Cell Cancer: Data From the Phase III JAVELIN Renal 101 Trial. Issue 17 (10th June 2022) - Rini, Brian I.; Moslehi, Javid J.; Bonaca, Marc; Schmidinger, Manuela; Albiges, Laurence; Choueiri, Toni K.; Motzer, Robert J.; Atkins, Michael B.; Haanen, John; Mariani, Mariangela; Wang, Jing; Hariharan, Subramanian; et al.
Abstract : PURPOSE: Both immune checkpoint inhibitors (ICIs) and vascular endothelial growth factor receptor (VEGFR) inhibitors are approved for advanced renal cell carcinoma treatment and can cause cardiovascular events (CVs); thus, combination therapy could lead to major adverse CV events (MACE). Cardiac serum biomarker assessment and imaging, including left ventricular ejection fraction (LVEF) monitoring, can be used to evaluate MACE. METHODS: To our knowledge, the JAVELIN Renal 101 trial, assessing avelumab plus axitinib versus sunitinib in patients with advanced renal cell carcinoma, is the first randomized study of ICI plus VEGFR inhibitor treatment to include prospective serial cardiac monitoring of LVEF and serum cardiac biomarkers. RESULTS: MACE (defined as grade ≥ 3 CV AEs) occurred in 31 patients (7.1%) in the combination arm and 17 patients (3.9%) in the sunitinib arm. Patients in the combination arm who had high baseline troponin T values were at higher risk of MACE versus patients with low values (MACE in 6/35 v 7/135, respectively; relative risk, 3.31; 95% CI, 1.19 to 9.22). This association was not observed in patients treated with sunitinib. Other CV baseline risk factors and serum cardiac biomarkers were not significantly predictive for MACE, although a trend toward an association with dyslipidemia was seen in the combination arm. No clinical value of on-treatment routine monitoring of LVEF in relation to MACE was observed. Although LVEF decline was significantly more frequent in the combination arm, most patients recovered, and decline was not associated with other significant cardiac events or symptoms. CONCLUSION: Patients with high baseline troponin T levels receiving ICI and VEGFR combinations may need to be monitored more closely for MACE. Routine monitoring of LVEF in asymptomatic patients is not recommended.